2016
DOI: 10.1371/journal.pone.0148583
|View full text |Cite
|
Sign up to set email alerts
|

Early Medieval Muslim Graves in France: First Archaeological, Anthropological and Palaeogenomic Evidence

Abstract: The rapid Arab-Islamic conquest during the early Middle Ages led to major political and cultural changes in the Mediterranean world. Although the early medieval Muslim presence in the Iberian Peninsula is now well documented, based in the evaluation of archeological and historical sources, the Muslim expansion in the area north of the Pyrenees has only been documented so far through textual sources or rare archaeological data. Our study provides the first archaeo-anthropological testimony of the Muslim establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The synergistic absence of gene flow in the European HOXB13-G84E (rs138213197) PCa mutation on chromosome 17 and the haplogroups (R1b1b2-M269 and R1a1a-M17) of the Y-chromosome could be elucidated by limitations in intermarriage across the Mediterranean Sea between European and North African population; which can be attributed to many factors notably the obvious cultural barriers and practices, despite the historical continuous reciprocity migration and movements that occur between the limitrophe of Europe and North Africa. In comparison with other studies on gene flow, our findings were in consonance with the results of earlier studies that reported the presence of sharp discontinuity and limited gene flow between Northwestern Africa and Iberian Peninsula employing high-resolution analysis of the human Y-chromosome [28][29]. Contrary, our results were in disagreement with the West-Eastern genetic cline reported on the differential admixture between Europe and North Africa neighboring population[30].…”
supporting
confidence: 84%
“…The synergistic absence of gene flow in the European HOXB13-G84E (rs138213197) PCa mutation on chromosome 17 and the haplogroups (R1b1b2-M269 and R1a1a-M17) of the Y-chromosome could be elucidated by limitations in intermarriage across the Mediterranean Sea between European and North African population; which can be attributed to many factors notably the obvious cultural barriers and practices, despite the historical continuous reciprocity migration and movements that occur between the limitrophe of Europe and North Africa. In comparison with other studies on gene flow, our findings were in consonance with the results of earlier studies that reported the presence of sharp discontinuity and limited gene flow between Northwestern Africa and Iberian Peninsula employing high-resolution analysis of the human Y-chromosome [28][29]. Contrary, our results were in disagreement with the West-Eastern genetic cline reported on the differential admixture between Europe and North Africa neighboring population[30].…”
supporting
confidence: 84%
“…S8 ). E–M81 (E1b1b1b1a), dating to ~ 2.8 ka (YFull, v.6.06.15), has been retrieved from early Islamic remains (seventh–eighth century CE) in southern France 38 , whereas the more derived E1b1b1b1a1 has been found in two individuals from an Islamic necropolis in the city of Valencia, dating to twelfth–thirteenth century CE 6 . E–M81 is today predominantly found in the Maghreb (where its average frequency is > 40%) and peaks in modern Berber populations, with frequencies reaching > 80% 39 41 , being almost fixed in some groups, such as the southern Moroccan Tachlhit-speakers 42 and the Chenini–Douiret and Jradou from Tunisia 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to low coverage, we could only assign him to a basal position within E1b1b1b1, but it is possible that he may belong to a more derived subclade. One possibility would be E1b1b1b1a (E–M81), which is the most common haplogroup amongst modern Berber males today 42 , 53 , and has been linked to Islamic remains in southern France 38 . Another would be its descendant E1b1b1b1a1-M183 lineage, identified in three Guanche males, in two Islamic individuals from Granada, and in an earlier sixth century CE male from the Visigoth phase of Pla de l'Horta, in Catalonia 6 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…On a general level, this burial provides additional evidence for the early adoption of specific Islamic burial rites which were followed even in remote locations. At present there are no examples of genetic studies from the region which relate to this period, the only genetic data which relates to early Islamic burials is the study of two individuals from the south of France 55 . Our results show early presence of Muslim Arabs in the Syrian countryside and provide more evidence of the Bedouin contribution to early Islamic society.…”
Section: Discussionmentioning
confidence: 99%